Fast, Easy, and Safe Establishment of Pneumoperitoneum in Laparoscopic Surgery: The Fingertip Technique - (:unkn) unknown (SOC LAPAROENDOSCOPIC SURGEONS, 2021)
Background and Objectives: There is no consensus on an ideal abdominal entry in laparoscopic surgery; as such, we aimed to assess the feasibility of the fingertip technique for safe entry and the establishment of pneumoperitoneum in transperitoneal laparoscopic surgery. Methods: We prospectively assessed 96 consecutive patients who underwent laparoscopic transperitoneal surgery between December 2018 and September 2019. For all patients, pneumoperitoneum was performed using the fingertip technique, which we recently defined. The duration of time for initial entry, the occurrence of gas leakage, and the complications were evaluated. Results: The median duration of initial entry was 90 (75 - 145) seconds. Pneumoperitoneum was established on the first attempt in all patients. Some events were encountered at the time of implementation of the fingertip technique, such as subcutaneous minor bleeding (5.2%) and gas leakage (4.1%). These events were controlled with cauterization and suturing. There was no visceral or major vascular injury in any patient case. Conclusions: The fingertip technique is a fast, safe, and feasible method for establishing pneumoperitoneum in transperitoneal laparoscopic surgery.
Keywords: Laparoscopy; Novel technique; Abdominalentry; Fingertip technique; Hasson; ENTRY